Strategi Peningkatan Portofolio Kredit Usaha Rakyat Pasca Pandemi Covid-19 Pada PT Bank Syariah Indonesia, Tbk Area Bekasi - Prabowo, Aji Patra Aria; Hubeis, Musa; Sudradjat, Sudradjat (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2024)
Micro, Small, and Medium Enterprises are one of important businesses in national economic growth, there are 195,553 MSMEs in the city and district of Bekasi based on KEMENKOP data and the Bank has an important role in the development of the sector in Indonesia. Bank Syariah Indonesia (BSI) is one of the Islamic financial institutions that provides financing through the People's Business Credit (KUR) program but with a portfolio still below conventional banks so a strategy is needed to increase the value of the KUR portfolio at PT BSI, Tbk. The research methodology uses a qualitative and quantitative mixed-method approach. The objectives of this study are (1) to analyze the current condition of MSMEs receiving KUR from PT BSI, Tbk, Bekasi Area, (2) to analyze the KUR portfolio of PT BSI, Tbk Bekasi Area, and (3) to develop a strategy to increase the KUR portfolio of PT BSI, Tbk Bekasi Area. The data used in this research are primary and secondary data. Primary data was obtained from selected respondents directly through questionnaires, interviews, and Focus Group Discussion. Secondary data is obtained from literature studies and BI internal and external data. The analysis used in this research is descriptive/situational analysis to explain existing phenomena and conditions and the Analytic Hierarchy Process (AHP). This study uses 211 customer data as a population. For analysis purposes, this study took a sample of 10% of the customer population. Sampling and research were taken in the Bekasi area because (1) The researcher's office is in the Bekasi area, (2) Based on the results of KEMENKOP data, the number of Micro, Small and Medium Enterprises in the Bekasi area is suitable for research, (3) Micro, Small and Medium Enterprises in Bekasi city can represent each KUR distribution segment. The results showed that most respondents did not experience difficulties in paying KUR loans and the strategy that was considered the most reliable in increasing the KUR portfolio of PT BSI, Tbk was to provide a special program for MSMEs that were bankable (KUR micro to KUR small class).